Історичні передумови формування дитячих закладів в умовах України - Скляренко, О. Ю. (КНУБА, 2019)
У статті розглянуто історичні передумови формування дитячих закладів в умовах України. На думку автора, актуальність питання обумовлена тим, що переважна більшість закладів дошкільної освіти України є створеною у попередній історичний час, що відбилося на архітектурних рішеннях їх будівель. Аналізується динаміка процесу формування закладів дошкільної освіти в Україні, визначаючи відповідним етапам архітектурні форми і їх особливості. Автор доходить висновку, що сучасні тенденції розвитку закладів дошкільної освіти визначають вироблення архітектурних проектів, заснованих на принципах гнучких архітектурно-планувальних рішень, складних композиційних схем і об’ємних просторових рішень. Потрібним є утворення типу дитячих закладів, пристосованих до умов сучасних багатоквартирних комплексів. In the article the historical preconditions of the formation of children's institutions in the conditions of Ukraine are considered. According to the author, the urgency of the issue is due to the fact that the vast majority of institutions of preschool education in Ukraine have been created in the previous historical period, which was reflected in the architectural decisions of their buildings. The dynamics of the formation of pre-school establishments in Ukraine is analyzed, defining the corresponding architectural forms and their peculiarities. The author concludes that the current trends in the development of pre-school establishments determine the development of architectural projects based on the principles of flexible architectural and planning decisions, complex composite schemes and bulk spatial solutions. Needed is the formation of kindergartens adapted to the conditions of modern multiapartment complexes.
The development of autodrome on the example of world experience.
Keywords: дитячі заклади; будівлі; історичний розвиток; Україна; children's institutions; buildings; Ukraine; historical development